2004
DOI: 10.1074/jbc.m407389200
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor-mediated Ca2+ Signaling in Striatal Medium Spiny Neurons

Abstract: Inositol 1,4,5-trisphosphate (InsP 3 ) and cAMP are the two second messengers that play an important role in neuronal signaling. Here, we investigated the interactions of InsP 3 -and cAMP-mediated signaling pathways activated by dopamine in striatal medium spiny neurons (MSN). We found that in ϳ40% of the MSN, application of dopamine elicited robust repetitive Ca 2؉ transients (oscillations). In pharmacological experiments with specific agonists and antagonists, we found that the observed Ca 2؉ oscillations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 65 publications
(135 reference statements)
7
53
0
Order By: Relevance
“…From these results, we concluded that dopamine potentiates glutamate-induced Ca 2ϩ signals in cultured WT and YAC128 MSNs via D 1 -class dopamine receptors. This conclusion is in agreement with our previous findings that the D 1 -class dopamine receptors, but not D 2 -class dopamine receptors, can greatly potentiate Ca 2ϩ responses in cultured rat MSNs (Tang and Bezprozvanny, 2004). Additional analysis revealed that the glutamate-induced Ca 2ϩ levels reached in the presence of 25 M SKF38393 were significantly ( p Ͻ 0.01) higher in YAC128 MSNs than in WT MSNs, consistent with potentiating effects of mutant Htt-128Q on intracellular Ca 2ϩ signals in striatal MSNs (Tang et al, 2005).…”
Section: Dopamine Potentiates Glutamate-induced Casupporting
confidence: 82%
See 2 more Smart Citations
“…From these results, we concluded that dopamine potentiates glutamate-induced Ca 2ϩ signals in cultured WT and YAC128 MSNs via D 1 -class dopamine receptors. This conclusion is in agreement with our previous findings that the D 1 -class dopamine receptors, but not D 2 -class dopamine receptors, can greatly potentiate Ca 2ϩ responses in cultured rat MSNs (Tang and Bezprozvanny, 2004). Additional analysis revealed that the glutamate-induced Ca 2ϩ levels reached in the presence of 25 M SKF38393 were significantly ( p Ͻ 0.01) higher in YAC128 MSNs than in WT MSNs, consistent with potentiating effects of mutant Htt-128Q on intracellular Ca 2ϩ signals in striatal MSNs (Tang et al, 2005).…”
Section: Dopamine Potentiates Glutamate-induced Casupporting
confidence: 82%
“…D 1 -class DARs are coupled to G s/olf , activation of adenyl cyclase, and cAMP production (Missale et al, 1998). PKA potentiates glutamate-induced Ca 2ϩ signals by facilitating activity of NMDAR (Levine et al, 1996;Flores-Hernandez et al, 2002) and InsP 3 R1 (Tang et al, 2003a;Tang and Bezprozvanny, 2004). In HD MSNs, NR2B-and InsP 3 R1-mediated Ca 2ϩ signaling is further facilitated by Htt exp (Zeron et al, 2002(Zeron et al, , 2004Tang et al, 2003bTang et al, , 2005.…”
Section: Dopamine Pathway Inhibitors and Treatment Of Hdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although signaling via the adenylyl cyclase-cAMP system is the principal mode of action, dopamine receptors also activate phospho-lipase C via the Gq/ 11 system and increase intracellular calcium levels [16,39]. Dopamine receptors also interact with glutamate receptors [4,21,44] and mobilize intracellular Ca 2+ stores [23,51].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Tang and colleagues (22) discovered a direct association between PP1 and InsP 3 R-1 and established that the association with PP1 facilitates dephosphorylation of PKA-phosphorylated InsP 3 R-1. These investigators established the role of AKAP9, a multifunctional PKA anchoring protein, in docking PKA and PP1 to InsP 3 R-1 (28) and in experiments with medium spiny neurons from DARPP-32 knock-out mice, demonstrated a regulatory role of DARPP-32 in dopamine-induced Ca 2+ oscillations (29). Although these results advance our understanding of crosstalk between cAMP and InsP 3 -mediated Ca 2+ signaling pathways in the brain, much less is known about the role of DARPP-32 in peripheral tissues, including lymphocytes, although DARPP-32 has been shown to increase the phosphorylation and activity of various ion channels (30).…”
Section: Measurement Of Intracellular Camentioning
confidence: 99%